Study on the Performance of a Thermo-Electric Generation Model with Two Different Materials of Heat Pipe-Heat Sink - Elghool, Ali; F., Basrawi; Hassan, Ibrahim; Thamir K., Ibrahim; Shaharin, A. Sulaiman; M., Ishak (EDP Sciences, 2018)
Heat sink lack of design is one reason that negatively affects the performance of thermoelectric modules. As compared to conventional cooling systems equipped with thermoelectric generators (TEG), heat pipe, heat sink has various points of interest. Heat pipe heat sink is the most, appropriate heat exchanger for medium temperature range under 300 oC. This paper demonstrates the effect of different materials of heat pipe-heat sink on the TEG performance. Two types of heat sinks were tested with TEG, one made from copper while the other from aluminium. The aim is to improve power output of TEG by an appropriate material of fins and metal block with heat pipes. The prototype was experimentally tested and the TEG cold side temperature, voltage and current were measured in both conditions, natural and forced convection. It was found that highest power output was achieved using copper heat sink in the case of forced convection, being 7.7 W whereas, lowest power output was obtained using aluminium heat sink in the case of natural convection, being 2.67 W. It is evident that copper heat sink is more effective than aluminium heat sink in terms of power output.,However, both types of heat sink needs optimisation in terms of power output, cost and economic efficiency, while the results shown in this paper are just in terms of power output